Pengaruh Brand Experience dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skin Game di Jabodetabek - Melani Aprilia; Angestika Wilandari (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
The skin care industry has attracted much attention in recent years. In line with the growth of the skincare industry, it encourages innovation in products used in skin care according to their functions. This study examines the effect of brand experience and product quality on purchasing decisions for Skin Game brand skin care products in Jabodetabek. The method used in this research is a descriptive quantitative approach with purposive sampling and determining the sample using the Lemeshow formula. The object of this research is consumers who use the skincare brand Skin Game in Jabodetabek, with 100 respondents. The results of this study reveal that the brand experience variable has a positive and significant effect on purchasing decisions from a significance result of 0.002, which means a sig value of 0.002 1.985. The results of hypothesis testing show that product quality positively impact purchasing decisions from a significance result of 0.000, which means a sig value of 0.000 t table of 1.985. The results of the F test showed that the F count is 61.024 with a significance value of 0.000. Brand experience and product quality simultaneously positively affect purchasing decisions for skin care products for the Skin Game brand. The result of the Coefficient determination Brand experience variables and product quality impact purchasing decisions by 55.7%. Keywords: Experience, Product Quality, Purchase Decision